A Comparison of the in Vitro and in Vivo Thrombogenic Activity of Factor IX Concentrates Using Stasis (Wessler) and Non-Stasis Rabbit Models - Prowse, C V; Williams, A E (Thrombosis and Haemostasis, 1980)
The thrombogenic effects of selected factor IX concentrates were evaluated in two rabbit models; the Wessler stasis model and a novel non-stasis model. Concentrates active in either the NAPTT or TGt50in vitro tests of potential thrombogenicity, or both, caused thrombus formation in the Wessler technique and activation of the coagulation system in the non-stasis model. A concentrate with low activity in both in vitro tests did not have thrombogenic effects in vivo, at the chosen dose. Results in the non-stasis model suggested that the thrombogenic effects of factor IX concentrates may occur by at least two mechanisms. A concentrate prepared from platelet-rich plasma and a pyrogenic concentrate were also tested and found to have no thrombogenic effect in vivo.These studies justify the use of the NAPTT and TGt50in vitro tests for the screening of factor IX concentrates prior to clinical use.
Keywords: Factor IX concentrate; Thrombosis; Intravascular coagulation